The electron injector for linac of the "NESTOR" storage ring - Aizatsky, M.I.; Kushnir, V.A.; Mytrochenko, V.V.; Perezhogin, S.A.; Zhiglo, V.Ph. (Вопросы атомной науки и техники, 2006)
Results of the bunching system design and electron motion simulation in the compact S – band injector are presented.
The injector consists of the low-voltage diode electron gun and bunching system based on the resonant system
with the evanescent oscillations. The amplitude of RF electrical field grows along the axis of the bunching system.
The resonance system optimization has been carried out that allows obtaining of the electron bunch with the
phase length less than 10° and energy spread less than 5% (for 70% particles) at the injector exit. В работе приведены результаты расчета группирующей системы и моделирование движения электронов в инжекторе S–диапазона. Инжектор состоит из низковольтной диодной электронной пушки и группирователя на основе резонансной системы с нераспространяющимися колебаниями. В устройстве реализовано такое распределение поля на оси, при котором его амплитуда нарастает от точки инжекции электронов до выхода группирователя. Проведена оптимизация резонансной системы, которая позволяет получить на выходе инжектора электронные сгустки с фазовой протяженностью меньше 10 градусов и шириной энергетического спектра меньше 5% (для 70% частиц). У роботі приведено результати розрахунку групуючої системи і моделювання руху електронів в
інжекторі S–діапазону. Інжектор складається з низьковольтної діодної електронної гармати та груповача на
основі резонансної системи з коливаннями, що не розповсюджуються. У пристрої реалізовано такий
розподіл поля на осі, при якому його амплітуда наростає від точки інжекції електронів до виходу груповача.
Проведена оптимізація резонансної системи, яка дозволяє одержати на виході інжектора електронні згустки
з фазовою протяжністю менше 10 градусів і шириною енергетичного спектру менше 5% (для 70% частинок).